Diversity of Mangroves and Crabs (Scylla spp.) in the Ketapang Indah Mangrove Forest, Aceh Singkil, Indonesia - Wintah; Kiswanto; Moh. Husein Sastranegara (Badan Penerbitan Fakultas Pertanian (BPFP), Fakultas Pertanian, Universitas Bengkkulu, 2026)
The mangrove forest is the habitat of several animals, such as crabs, gastropods, and bivalves. Some species of animals live around mangrove roots, both in hard and soft (muddy) substrates; among them are mangrove crabs. Mangrove crabs (Scylla spp.) belong to the Portunidae family and are found in nearly all coastal waters, particularly on coastal areas covered with mangroves. This study aims to assess crab diversity in the Ketapang Indah mangrove forest in Aceh Singkil. Sampling points for collecting mangrove crabs were determined using the random sampling method. Crabs were collected using traps with a diameter of 45 cm². Traps were placed randomly at three locations within a 10 m × 10 m area in each mangrove sampling plot. The results of the study revealed a diversity of five mangrove species: Avicennia marina, Rhizophora mucronata, Rhizophora apiculata, Rhizophora stylosa, and Sonneratia alba. The diversity of mangrove crabs found at the study site consisted of three species: Scylla serrata, Scylla olivacea, and Scylla paramamosain. The overall species diversity of mangroves and crabs were moderate category. Although the mangrove ecosystem provides suitable habitat for Scylla spp., mangrove stand density were not reflected in crab density. Mud crab abundance is influenced more by habitat quality than by mangrove density alone. Conservation efforts should also emphasize maintaining habitat complexity and environmental quality besides increasing mangrove stand density to support sustainable mud crab populations. Keywords: biodiversity, crabs, density, mangroves